Electrocatalytic materials for solid polymer electrolyte water electrolyzers. Issue 5 (December 2020) - Pushkarev, A S; Pushkareva, I V; Akelkina, S V; Kozlova, M V; Grigoriev, S A; Kuleshov, N V; Bessarabov, D G
Abstract: In the present work the activity and stability of the IrOx /TiOx catalyst obtained by the polyol approach in the oxygen evolution reaction (OER) were studied in comparison with the commercial analogue IrOx . Electrochemical studies were provided, including accelerated stress testing. The synthesized IrOx /TiOx catalyst demonstrated higher OER activity and stability than the commercial IrOx, and the obtained results allow to suggest and discuss possible mechanisms of the studied catalysts degradation. Tests of membrane-electrode assemblies based on synthesized IrOx /TiOx catalysts in SPE water electrolyzer demonstrate the possibility to significantly reduce the noble metal content on the anode..